Recall Bias in Client-Reported Outcomes in Canine Orthopaedic Patients Using Clinical Metrology Instruments - Pappa, Eirini; Maddox, Thomas W.; Crystal, Edward; Comerford, Eithne J.; Tomlinson, Andrew W. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to determine the accuracy of client recollection of their dogs' preconsultation status using clinical metrology instruments such as the Liverpool Osteoarthritis in Dogs (LOAD) and Canine Brief Pain Inventory (CBPI) questionnaires in dogs presenting to a referral orthopaedic clinic.Study Design This is a longitudinal prospective cohort study of client-owned dogs presenting for investigations of lameness (n = 217). LOAD and CBPI questionnaires were completed by the owners at the first consultation (T0). Owners were contacted at 2 (T1), 6 (T2), and 12 (T3) months and asked to recall their dogs' T0 status by completing another LOAD and CBPI questionnaire. The agreement between the T0 and recalled LOAD and CBPI scores was determined using the two-way mixed effects intraclass correlation coefficient (ICC). The Wilcoxon signed-rank test was used to determine the difference between scores.Results For the LOAD scores, there was moderate agreement between T0 and T1 (ICC: 0.64) and T0 and T2 (ICC: 0.53) scores and poor agreement between T0 and T3 (ICC: 0.496). For the CBPI Pain Severity Scores, there was poor agreement between T0 and all three subsequent time points (ICC < 0.5). For the CBPI Pain Interference Scores, there was moderate agreement between T0 and T1 (ICC: 0.57) and T2 (ICC: 0.56) scores and poor agreement between T0 and T3 (ICC: 0.43).Conclusion The LOAD and CBPI questionnaires are subject to recall bias. Studies reporting retrospectively acquired CMI data should be interpreted with caution.
Keywords: recall bias; LOAD; CBPI; clinical metrology instrument (CMI)